2009
DOI: 10.1038/eye.2009.60
|View full text |Cite
|
Sign up to set email alerts
|

Transplantation of cultivated oral mucosal epithelial cells for severe corneal burn

Abstract: Purpose To access the feasibility of using cultivated oral mucosal epithelial cell transplantation (COMET) for the management of severe corneal burn. Methods COMET was performed to promote re-epithelialization in two eyes with acute alkaline burn and one eye with chronic alkaline burn, and to reconstruct the ocular surface in two eyes with chronic thermal burn. Autologous oral mucosal epithelial cells obtained from biopsy were cultivated on amniotic membrane. Immunoconfocal microscopy for keratins and progenit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
74
0
4

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(85 citation statements)
references
References 29 publications
4
74
0
4
Order By: Relevance
“…COMET also can be used as an alternative treatment to promote reepithelialization and reduce inflammation in acute corneal chemical or thermal injuries. 13 Furthermore, long-term existence of transplanted oral mucosal stem/progenitor cells on the ocular surface also supports the rationale for clinical use of cultivated epithelial transplantation. 3 However, even after successful autologous COMET, various degrees of superficial corneal neovascularization (NV) can be detected beneath the transplanted epithelial sheet.…”
mentioning
confidence: 91%
See 1 more Smart Citation
“…COMET also can be used as an alternative treatment to promote reepithelialization and reduce inflammation in acute corneal chemical or thermal injuries. 13 Furthermore, long-term existence of transplanted oral mucosal stem/progenitor cells on the ocular surface also supports the rationale for clinical use of cultivated epithelial transplantation. 3 However, even after successful autologous COMET, various degrees of superficial corneal neovascularization (NV) can be detected beneath the transplanted epithelial sheet.…”
mentioning
confidence: 91%
“…3 However, even after successful autologous COMET, various degrees of superficial corneal neovascularization (NV) can be detected beneath the transplanted epithelial sheet. [13][14][15][16] Clinically, corneal NV following total LSCD is the most severe type, and the molecular mechanisms regulating NV formation and restoration of corneal avascularity after CLET have been reviewed extensively. 17,18 Recently, in vitro studies using cultivated oral and corneal epithelial cells from either humans [19][20] or rabbits 20,21 have shown that decreased expression of thrombospondin-1 (TSP-1) 20 and soluble fms-like tyrosine kinase-1 (sFlt-1), 22 and increased secretion of fibroblast growth factor-2 (FGF-2) 21 may be responsible for the enhanced angiogenic potential after COMET.…”
mentioning
confidence: 99%
“…24 Investigations on this variable have not been possible to date as there is no single, specific molecular marker for epithelial SCs, especially, as the known markers are not exclusive. 7,9,11,25 The reported putative markers for BMESCs include the transcription factor p63, 7 ATP-binding cassette transporter (ABCG2), 9,11 lowaffinity NGF receptor p75, 25 and b1 integrin. As these markers are not exclusive to SCs, it is essential to develop a specific method to identify and quantify the BMESCs.…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9] But the SC content in cultured buccal mucosal epithelium has not been analyzed, except for the reports on the expression of the putative SC markers like p63, ABCG2, p75, and b1 integrin that are not exclusive to SCs. 10,11 Other markersFa6 integrin and melanomaassociated chondroitin sulfate proteoglycan (MCSP)Fwere found to be restricted to clusters of cells in the mucosal papillay tips. 12 Previously, we have demonstrated that the two parametersFhigh expression of nuclear protein p63 and a greater nucleus/cytoplasmic (N/C) ratio in combinationFidentified a subset of limbal epithelial cells with SC phenotype.…”
Section: Introductionmentioning
confidence: 99%
“…COMET has been shown to be successful in restoring the corneal surface with follow-up times of up to 35 months [36][37][38][39][40][41][42][43]. A summary of the reported studies in human patients to date is shown in Table 1.…”
Section: Alternative Stem Cell Sourcesmentioning
confidence: 99%